Exploring the tuberculosis medication program in Indonesia as perceived by patients and their families: A qualitative study - Imelda Liana Ritonga; Setyowati Setyowati; Hanny Handiyani; Astuty Yuni Nursasi (Belitung Nursing Journal, 2023)
Background: Tuberculosis (TB) remains a significant public health challenge in Indonesia, with the country experiencing one of the highest numbers of lost cases in TB management. Therefore, there is a need to identify the underlying reasons for this problem. Objective: This study aimed to explore the experiences of TB-diagnosed patients and their families during the time of diagnosis and while undergoing the TB medication program. Methods: This study employed a qualitative descriptive-interpretive approach. The study was conducted in government community health centers (CHC) from May 2022 to July 2022. A total of 22 participants, consisting of 12 TB-diagnosed patients and ten family members, were included in the study. Data were collected through focus group discussions and analyzed thematically. Results: Five themes were developed: (1) Delay in tuberculosis diagnosis, (2) Delay in starting TB treatment, (3) High willingness of patients and their families to recover, (4) Understanding that TB is an infectious disease, and (5) Factors affecting patient recovery. Conclusion: The study findings might contribute to the National TB elimination program. It is recommended that all health workers practicing in the community should be involved in the TB program to improve its management. Collaboration between multiple sectors in the community can also provide an advantage in solving TB problems by increasing new case detection. Additionally, it is suggested that all nurses working with TB patients establish rapport with health cadres and patients’ families to enhance medication adherence in patients.